Legitimacy and Reflexivity in International Investment Arbitration: A New Self-Restraint? - David Schneiderman (Oñati Socio-Legal Series)
There are at least two views within investment arbitration about how to respond to legitimation problems associated with inconsistent rulings, latitudinal interpretations, and arbitral bias and conflicts of interest. Some prefer to keep the regime on course and not respond to these outside perturbations. Others prefer to take into account external influences, such as human rights and environmental commitments, in the course of investment treaty interpretation. Both understand that, whatever the response, these questions will be determined by lawyers, scholars, and arbitrators operating within the system of international investment law and not by actors operating outside of it. Both views, in other words, are congenial to systems-theoretic accounts. As articulated by Teubner, there is a proliferation of functional legal sub-systems, developing autonomously of states, each of which, in the course of maximizing internal rationality, potentially is on a collision course with other operative sub-systems. These can only be forestalled if sub-systems act reflexively by devising strategies of self-limitation that selectively internalize objections emanating from external spheres. As this maps on to self-understandings of actors operating within investment arbitration, this paper takes up systems theory as a heuristic for assessing the regime’s responsiveness to outside influences. In order to take stock of the degree of reflexivity, the paper examines the direction investment law is taking in a few key areas: first, in the shift in emphasis away from expropriations (the ‘takings rule’) to the fair and equitable treatment standard, which is performing similar functions; second, in the attempt to merge global standards by embracing World Trade Organization Appellate Body decision making; and third, the hesitant embrace of proportionality doctrine as a means of weighing public interests into the equation. These moments of reflexivity turn out to be modest in reach and so unlikely to calm objections emanating from states and social movements. What likely will be necessary is intervention into and steering by states of the regime, an intervention that is anathematic to Teubner’s system-theoretic account.